Study on antipyretic property of the leaves of Ligustrum robustum - ., Vanlalhruaii; P., Naveen (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Thorough pharmacological experiments on various plants used in traditional medicines are in progress in order to establish their effectiveness and safety. But modern drugs or conventional medicines are often viewed as impersonal, emphasizing crisis intervention. Keeping in view the above idea, the present study is undertaken on the plant Ligustrum robustum to explore its antipyretic property in albino rats. Methods: Healthy young albino rats weighing between 100-250gm were obtained for the study. The animals were divided into five groups with six animals in each group. Pyrexia was induced by subcutaneous injection of dried yeast in 2% gum acacia in normal saline at a dose of 20ml/kg body weight below the nape of the neck in albino rats. The antipyretic activity of the aqueous extract of Ligustrum robustum was tested by yeast induced method. The data were subjected to ANOVA followed by Dunnett’s ‘t’ test for statistical significance between different groups. Results: Ligustrum robustum in doses of 100mg/kg, 200mg/kg and 400mg/kg significantly reduced the temperature (p<0.05 to 0.01) in the 3rd and 4th hour after drug administration. Conclusions: Present study concludes that the aqueous extract of the leaves of Ligustrum robustum showed significant antipyretic property in the standard experimental animal models.